Piece of cake [videorecording (DVD)] - Gaines, Boyd; Dudgeon, Neil; Parker, Nathaniel, 1962-; Toynton, Ian; Robinson, Derek, 1932 April 12- (BFS Video, 1994)
The adventures, heartaches and rites of passage of the fighter pilots of RAF Hornet Squadron during World War II.